1996
DOI: 10.1002/ana.410390203
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of vitamin E, riluzole, and gababapentin in a transgenic model of familial amyotrophic lateral sclerosis

Abstract: Familial amyotrophic lateral sclerosis (FALS) has been linked in some families to dominant mutations of the SOD1 gene encoding Cu,Zn superoxide dismutase (Cu,ZnSOD). We have used a transgenic model of FALS based on expression of mutant human Cu,ZnSOD to explore the etiology and therapy of the genetic disease. Expression of mutant, but not wild-type, human Cu,ZnSOD in mice places the brain and spinal cord under oxidative stress. This causes depletion of vitamin E, rather than the typical age-dependent increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
322
4
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(355 citation statements)
references
References 52 publications
19
322
4
6
Order By: Relevance
“…Previous research into the pathogenesis of ALS supports the hypothesis that the production of free radicals precipitates, or at least facilitates, motor neuron loss, while multiple antioxidants attenuate this deleterious progression [ (Gurney et al 1996;Henderson et al 1996)]. By crossing the SOD G93A mouse model of ALS with a reporter of ARE activation, we were able to discern that the Nrf2-ARE pathway is indeed active within the hindlimb muscle at a very early timepoint (30 days, Figure 1).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous research into the pathogenesis of ALS supports the hypothesis that the production of free radicals precipitates, or at least facilitates, motor neuron loss, while multiple antioxidants attenuate this deleterious progression [ (Gurney et al 1996;Henderson et al 1996)]. By crossing the SOD G93A mouse model of ALS with a reporter of ARE activation, we were able to discern that the Nrf2-ARE pathway is indeed active within the hindlimb muscle at a very early timepoint (30 days, Figure 1).…”
Section: Discussionmentioning
confidence: 57%
“…In humans, as well as animal models, it has been clearly shown that oxidative stress plays a central role in the progression of this motor neuron loss, possibly in concert with a chronically enhanced excitotoxin profile [ (Rothstein et al 1990;Gurney et al 1996;Andrus et al 1998;Heath and Shaw 2002;Agar and Durham 2003)]. Five to 10% of all human ALS cases have a familial cause (fALS), of which about 20% are caused by a mutation in the gene encoding Cu/Zn superoxide dismutase (SOD1) [ (Rosen 1993;Gurney et al 1994)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it resulted in a significant prolongation for 16 and 11 days in survival of female and male SOD1 G93A mice, respectively. Therefore, sigma-1R modulation produces important functional benefits in terms of spinal MN function, locomotion, and survival in the SOD1 G93A mouse model, even comparatively better than silencing the mutant SOD1 expression [38] or other pharmacological treatments previously reported [39], such as riluzole [40].…”
Section: Discussionmentioning
confidence: 94%
“…However, the overall effect in ALS patients was transient in that the survival curves were unaffected when examined in prolonged follow up studies (47,48). In ALS animal models (S2), Riluzole treatment (100µg/mL water) during the presymptomatic stage was initially shown to exert no effect on delaying the onset of disease, but did significantly extend survival by 13-15 days (49). A follow-up study showed a dose-dependent preservation of motor function, while exhibiting an identical positive effect of survival at doses of 24-44 mg riluzole/kg body weight/day of 12-13 days (50).…”
Section: Murine Models Of Familial Alsmentioning
confidence: 99%